PENGARUH BUAH PINANG TERHADAP SIFAT MIKROBIOLOGIS DAN KIMIA NIRA GEWANG SERTA SIFAT FISIK DAN ORGANOLEPTIK GULA CAIR - Lalel, Herianus J. D.; Mukkun, Lince; Nalle, Ryan P. I.; Bonny, Alexandra V. P. (MEDIAGRO, 2024)
Gebang (Corypha utan Lamk) sap is increasing in its economical value for people in Timor Island. The presence of microbial contaminants reduces its quality. Therefor, it needs prevention by applying a safe antimirobes food additive. A research has been conducted by using a Completely Randomized Design (CRD) for 4 treatments with 3 replications. The treatments are control (P0): gebang sap without areca nut powder, gebang sap with 2% areca nut powder , gebang sap with 4% areca nut powder (P2), and gebang sap with 6% areca nut powder (P3). Parameters observed were Total Plate Count (TPC), acidity (pH),  and Total Soluble Solids (TSS) of the sap, and Water Activity (aW) and organoleptics of the liquid sugar. The result showed that the addition of areca nut powder reduced total microbes, maintained the sap pH and increased TSS of the sap as well as reduced the aW of liquid sugar; however, it lowerred the organoleptic properties of the sugar.